FEATURES OF THE TRAINING PROCESS OF VOLLEYBALL PLAYERS OF VARIOUS QUALIFICATIONS - Akbar Abdiravupovich, Khakkulov (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the fundamentals of the technique of teaching the technique of playing volleyball and the development of physical qualities in students of different qualifications, necessary for them to effectively master the technique of playing and achieve high results in the process of physical education. Indicates the correct selection of methods, principles and means, are used in the classroom as an effective component of the formation of skills in mastering techniques and tactical actions.